Concept Fallibility in Organizational Science - Yg, Chimezie A. B. Osigweh (Academy of Management Review, 1989)
This paper extends existing social and behavioral science knowledge by placing explicit emphasis on concept-formation issues as they pertain to organizational science. Moreover, the paper (a) introduces in a detailed manner the notions of concept traveling and concept stretching, (b) provides a clear treatment of various conceptual abstraction levels, (c) articulates and offers the negation approach, and (d) shows how to attain the abstraction levels via the use of the negation approach to concept formation.